DYNAMIC SAFETY INTERACTIONS FOR IMPROVING QUALITY OF WORK LIFE: A PROPOSED CONCEPTUAL FRAMEWORK FOR ENGINEERS IN MANUFACTURING INDUSTRIES - Norizan Baba Rahim (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
In Malaysia’s manufacturing industry, workplace accidents and injuries are a big problem. This industry has made only minor progress in terms of reducing fatalities and significant injuries. The fatal injury rate decreased marginally; however, the previous year’s severe injury rate stayed unchanged. (Department of Occupational Safety and Health (DOSH), 2021). As a result, manufacturing safety continues to be a severe issue in Malaysia. The organisational nature of industrial accidents has been highlighted in safety literature, and empirical study has focused on determining the organisational, managerial, and environmental elements that influence accident causation. The majority of prior works have emphasised the concept of safety culture (or safety climate). Scholars have recently begun to look into additional organisational elements, such as the impact of organisational environment, leadership style, and occupational stressors on industrial accidents. This study presents a conceptual framework to investigate the interaction between safety climate and safety behaviour in Malaysia’s manufacturing sector, with the goal of developing more effective safety interventions to reduce accidents.